Efecto de diversas dosis de óxido cuproso y zineb aplicados a bajo volumen en el control de la Monilia en el cacao - Delgado, J.C. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
An experiment was made in 1959 in Pichilingue, Ecuador, to control Monilia disease in cacao with two different dosis of cuprose oxide and zineb. Cuprous oxide was more effective than zineb. The lower dosis of cuprous oxide produced a lower number of diseased cacao pods. Both fungicides did not affect cacao flowering and fruiting.